Treatment of neurolept-induced tardive dyskinesia - Jankelowitz SK (Dove Medical Press, 2013)
Stacey K Jankelowitz Central Clinical School, University of Sydney, Sydney, NSW, Australia Abstract: Tardive dyskinesia (TDK) includes orobuccolingual movements and “piano-playing” movements of the limbs. It is a movement disorder of delayed onset that can occur in the setting of neuroleptic treatment as well as in other diseases and following treatment with other drugs. The specific pathophysiology resulting in TDK is still not completely understood but possible mechanisms include postsynaptic dopamine receptor hypersensitivity, abnormalities of striatal gamma-aminobutyric acid (GABA) neurons, and degeneration of striatal cholinergic interneurons. More recently, the theory of synaptic plasticity has been proposed. Considering these proposed mechanisms of disease, therapeutic interventions have attempted to manipulate dopamine, GABA, acetylcholine, norepinephrine and serotonin pathways and receptors. The data for the effectiveness of each class of drugs and the side effects were considered in turn. Keywords: tardive dyskinesia, treatment, neuroleptic agents